A Study of Energy Efficiency and Mitigation of Carbon Emission: Implication of Decomposing Energy Intensity of Manufacturing Sector in Taiwan - Huang, Yu-Kai; Hsu, Jyh-Yih; Sun, Lih-Chyun (International Journal of Energy Economics and Policy, 2017)
This paper applies the Logarithmic Mean Divisia Index (LMDI) approach to examine aggregate energy intensity of the manufacturing sector in Taiwan from 1982 to 2014. We decompose aggregate energy intensity into three effects, which are the fuel mixed effect, the sectoral energy intensity effect, and the substructural effect. The results show that aggregate energy intensity is highly correlated with carbon intensity in Taiwan. Moreover, the aggregate energy intensity is mainly driven by sectoral energy intensity effect. The influence of the substructural effect and fuel mixed effect on improving the aggregate energy intensity has become larger in the recent years. The policy implication of study results suggests that internalizing the costs of carbon emission, creating incentives to invest energy-saving technology, establishing a fair and efficient electricity market are needed in Taiwan. Keywords: Logarithmic mean Divisia index, Energy intensity, Carbon intensity, Structural change, Fuel mixed effect JEL Classifications: O1, O2, Q4, Q5